RETROFIT AND CONVERSION OF R-22 CHILLER TO R-290 AND ITS PERFORMANCE COMPARISON - Suwono, Aryadi; Tandian, N. P; Pasek, A. D; Hardianto, T; Soelaiman, T. A Fauzi (Mesin, 1999)
The retroï¬t and conversion of a R22 chiller to R290 was done on an AC chiller Carrier Type 30-GB-070-910. The retroï¬t of chiller was mainly the implementation of safety features and conversion to HC refrigerant. A series of measurements to evaluate its performance has been carried out on the same chiller for both eases i.e. before and after conversion, while it was in use. The resulting data analysis revealed that the chiller performed better with HC refrigerant compare to its previous condition. Retroï¬tting procedure, refrigerant conversion, test procedure and data analyses are discussed in this paper.